2019
DOI: 10.1016/j.memsci.2019.117313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a nanoporous lyotropic liquid crystal polymer membrane for the treatment of hydraulic fracturing produced water via cross-flow filtration

Abstract: Current commercial nanofiltration and reverse osmosis membranes are limited in scope and performance due to their physicochemical properties. Desalination of hydraulic fracturing wastewater poses a particular challenge to membrane filtration given the high concentrations of both organic compounds and salts present in these waters. The recently-developed nanoporous, bicontinuous cubic, lyotropic liquid crystal, thin-film-composite polymer membrane (TFC QI membrane), having unique physicochemical properties, ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 62 publications
(126 reference statements)
0
13
0
Order By: Relevance
“…13,14 Membranes prepared from polymerized lyotropic liquid crystals (LLCs), for example, possess subnanometer transport channels that retain mono-and divalent ions. 15,16 Block copolymer (BCP) self-assembly has been used to manufacture ultrafiltration (UF) membranes possessing monodisperse pores with controlled functionality 8,13,17−21 but low ion retention due to relatively large pores. To reduce the BCP membrane pore size into the NF regime, 19 researchers utilized block(s) that swell into the pore upon postfunctionalization.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Membranes prepared from polymerized lyotropic liquid crystals (LLCs), for example, possess subnanometer transport channels that retain mono-and divalent ions. 15,16 Block copolymer (BCP) self-assembly has been used to manufacture ultrafiltration (UF) membranes possessing monodisperse pores with controlled functionality 8,13,17−21 but low ion retention due to relatively large pores. To reduce the BCP membrane pore size into the NF regime, 19 researchers utilized block(s) that swell into the pore upon postfunctionalization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Self-assembly is a powerful tool for fabricating nanostructured membranes with uniform pore size, controlled surface/pore chemistry, and exceptional performance. , Membranes prepared from polymerized lyotropic liquid crystals (LLCs), for example, possess subnanometer transport channels that retain mono- and divalent ions. , Block copolymer (BCP) self-assembly has been used to manufacture ultrafiltration (UF) membranes possessing monodisperse pores with controlled functionality ,, but low ion retention due to relatively large pores. To reduce the BCP membrane pore size into the NF regime, researchers utilized block(s) that swell into the pore upon postfunctionalization. This enabled charge-based separations for ∼1 nm molecules or ∼2 nm pores that remained stable over a broad pH range .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Dischingeret al [52] demonstrated the crossflow study of this thin film composite Q I membrane as well as its fouling study for the first time. In this study, the authors used this membrane to filter pre-treated produced water using crossflow filtration for 66 h. Further, results revealed that, both in respect of selectivity and thickness-normalized water flux, this membrane exhibited its performance in industrially relevant conditions.…”
Section: Lyotropic Liquid Crystal-based Water Treatment Membranesmentioning
confidence: 95%
“…A recently developed membrane TFC Q(I) with unique physicochemical properties was tested for its performance in treating hydraulic fracturing produced water using cross-flow filtration (Dischinger, Rosenblum, Noble, & Gin, 2019). The nanoporous lyotropic liquid crystal polymer membrane was effective in recovering organic matter and alleviating fouling.…”
Section: Membrane Technologymentioning
confidence: 99%